Opening Remarks: Celebrating Western New England's 60th Anniversary: Hans Loewald's Enduring Contribution to Psychoanalysis: The Western New England Psychoanalytic Society Symposium, March 28th, 2015. Issue 1 (1st January 2018) - Cappiello, Angela
ABSTRACT: The introduction of the 2015 Western New England Psychoanalytic Society Spring Symposium addresses Hans Loewald as an innovator and pivotal contributor to modern psychoanalysis. The opening remarks of the symposium give a glimpse into the vibrant analytic atmosphere that permeated the Western New England Institute for Psychoanalysis (WNEIP), at the forefront of training and professional analytic development from the very start. In 1955 Hans Loewald joined this newly founded WNEIP; his revolutionary approach has inspired generations of analysts, and his work has been an essential component of the history of the Western New England Psychoanalytic Society.